“Dosis de fertilización con óxido de magnesio en plántulas de palma aceitera (elaeis guineensis jacq.) en la etapa de vivero en la empresa plantaciones de Ucayali S.A.C.” - Amasifuén Tuanama, Diana (2016)
This research entitled" Rates of fertilization with magnesium oxide in seedlings of oil palm (Elaeis guineensis Jacq.), in the nursery stage in the company Plantations Ucayali SAC ", implemented in the company in question, whose objectives were: 1) get seedlings of oil palm (Elaeis guineensis Jacq), with good growth and vegetativa development under nursery conditions. 2) evaluate the effect of four doses of magnesium oxide when supplied to Q - MAG® on growth and development of oil palm seedlings 3) Determine which of the dose of magnesium oxide is optimal to correct Mg deficiency the cultivation of oil palm. The design was the randomized complete (RCBD) with three replications and four treatments repetition for TO (control), T1 (9 g of Q -MAG), T2 (13 g of Q -MAG), T3 block ( 17 g of Q -MAG), using 20 experimental units per treatment, planting distance was O, 70 m between rows and O, 60 m between plants respectively The T3 ( 17 g of Q -MAG ) , treatment obtained the highest averages with respect to the variables plant height, leaf length , number of leaves, stem diameter, root length, number of roots and dry matter Total with 86,86 cm, 65,96 cm long, 13,98 leaves, 65,26 mm diameter 77,33 cm long root 26,33 , and 202,67 g respectively, weight, this is a consequence of increasing dose of Q -MAG applied to different treatments . Keywords: oil palm, nursery, seedlings, Dose, Q -MAG, Elaeis guineensis.